Comparsion of Activities of Fatty Acyl Desaturases and Elongases Among Six Teleosts With Different Feeding and Ecological Habits - Xie, Dizhi; Ye, Jialing; Lu, Meisong; Wang, Shuqi; You, Cuihong; Li, Yuanyou (Frontiers in Marine Science, 2020)
Fatty acyl desaturases 2 (Fads2) and elongases of very-long-chain fatty acid 5 (Elovl5) are two key enzymes involved in the biosynthesis of long-chain polyunsaturated fatty acids (LC-PUFAs), and their activities determine the LC-PUFA biosynthetic ability of teleost. In order to investigate the relation of enzymic activities with fish’s feeding habits and ecological habits, the activities of Fads2 and Elovl5 were compared among six teleosts, namely, freshwater carnivorous mandarin fish (Siniperca chuatsi), freshwater herbivorous grass carp (Ctenopharyngodon idellus), marine carnivorous orange-spotted grouper (Epinephelus coioides), marine herbivorous rabbitfish (Siganus canaliculatus), anadromous Atlantic salmon (Salmo salar), and catadromous Japanese eel (Anguilla japonica). Among them, the enzymatic features of Fads2 and Elovl5 from the last five fish species have been characterized, whereas those of S. chuatsi were unknown. And thus, the coding sequences (CDSs) of S. chuatsi fads2 and elovl5 (elovl5a and elovl5b) were isolated, and their functions were further characterized by heterologous expression in yeast. The results showed that S. chuatsi Fads2 has a monofunctional Δ6 desaturase and that Elovl5a has a higher activity toward C18–C20 PUFAs than has Elovl5b, which showed a noteworthy activity toward C22 PUFAs. The comparison of enzymatic activities among the six teleosts showed that the Δ6 Fad and Elovl5 activities varied markedly among fish species; in particular, the activity of Δ6 Fad in C. idellus, S. canaliculatus, and A. japonica was significantly higher than that in S. chuatsi, S. salar, and E. coioides. For C18 PUFA substrates, A. japonica Elovl5 has a higher elongation than has the other tested fish, and it exhibits a higher activity toward the C20 PUFAs. The results suggest that the Δ6 Fad activity is influenced by both feeding habits and ecological habits, whereas the Elovl5 activity was more affected by the feeding habits. These data enrich our knowledge on LC-PUFA biosynthesis diversity of fatty acid desaturation and elongations in teleosts and provide guidance for the choice of dietary PUFA precursors for farmed fish.